The Flora of Uzbekistan Project - Sennikov, Alexander N.; Tojibaev, Komiljon Sh.; Khassanov, Furkat O.; Beshko, Natalya Yu. (Phytotaxa, 2016)
A new project, ‘Flora of Uzbekistan’, is announced to start with publication in 2017. It aims at publishing a multi-volume taxonomic treatment of vascular plants of Uzbekistan, with complete synonymy, nomenclature, distribution data, descriptions and identification keys. The taxonomic treatment is supported by an extensive database of distribution records, used to generate distribution maps. The background information for the Flora is provided, and the structure and the format of the work are outlined.